Composite pipeline material as well as preparation method and application thereof
By using composite pipeline materials stacked from the inside to the outside, and using the combination of epoxy resin and basalt fibers, the corrosion problem of stray current on metal buried pipelines is solved, efficient corrosion resistance and mechanical strength improvement is achieved, and the safety and load-bearing capacity of the pipeline are ensured.
Patent Information
- Application Number
- CN202411823286.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art cannot effectively suppress the corrosion of stray currents on metal buried pipelines, resulting in the accelerated corrosion rate of pipelines, and the potential for leakage and failure, affecting safety and load-bearing capacity.
The composite pipe materials stacked from the inside to the outside are adopted, including the inner surface layer, the inner fiber cloth reinforcement layer, the inner fiber winding layer, the fiber reinforcement structure layer, the outer fiber cloth reinforcement layer, the outer fiber winding layer and the outer protective layer. The combination of epoxy resin and basalt fibers is used to improve electrical insulation and anti-stroke current capabilities.
The composite pipe material significantly reduces corrosion caused by stray currents, improves the corrosion resistance and mechanical strength of the pipe, extends the service life of the pipe, and enhances safety and load-bearing capacity.
Smart Images

Figure CN119659098A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of pipeline materials, and in particular relates to a composite pipeline material and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of the economy, the construction of the power industry, especially high-voltage and ultra-high-voltage AC transmission lines, and high-speed railways, urban subways, light rails, oil and gas pipelines, and traditional metal buried pipelines have formed a "public corridor". In the narrow area of the "public corridor", transmission lines, electrified railways, and metal buried pipelines are crossed and parallel. High-speed railways and transmission lines generate AC stray current interference on metal buried pipelines through conduction and induction. Subways and light rails are both powered by electric traction, and basically use direct current. It is a system in which the traction substation supplies power to electric vehicles through the traction network laid along the line. It is mainly powered by the overhead positive contact network, and the walking track is used as the negative return conductor. During operation, a lot of current does not return to the traction substation along the return track or does not return to the traction substation at all, but flows to the low potential of the earth, forming stray current. Stray current corrosion has the characteristics of direct electrolysis of metals, so its corrosion rate is 10n times the uniform corrosion rate of the pipeline in its natural state, and even causes hidden dangers such as corrosion perforation, which reduces the inherent safety and carrying capacity of the pipeline, resulting in frequent pipeline leakage and failure accidents, causing property losses and threatening personal safety. The frequent occurrence of oil and gas pipeline corrosion caused by stray current has become a major risk threatening the safe operation of metal buried pipelines.
[0003] In the protection of buried pipelines, cathodic protection is a technology that is most closely integrated with the application of coating protection and can significantly inhibit corrosion at the damaged parts of the pipeline anti-corrosion coating. However, when the buried pipeline is disturbed by stray currents, traditional anti-corrosion measures cannot effectively inhibit corrosion. At present, drainage measures such as direct grounding, negative potential grounding and solid decoupler grounding are usually used for stray currents. However, the efficiency of drainage is low, and for areas with dense pipelines, the drainage range is limited, resulting in poor results. Therefore, developing a new type of composite material pipeline that is resistant to stray currents and electrochemical corrosion to replace metal buried pipelines is an effective way and method to solve this problem. Summary of the invention
[0004] In view of this, the present invention provides a composite pipeline material and a preparation method and application thereof. The composite pipeline material provided by the present invention has good electrical insulation and can reduce pipeline corrosion caused by stray current when used as a buried pipeline.
[0005] In order to solve the above technical problems, the present invention provides a composite pipe material, which comprises, from inside to outside, an inner surface layer 1, an inner fiber cloth reinforcement layer 2, an inner fiber winding layer 3, a fiber reinforcement structure layer 4, an outer fiber cloth reinforcement layer 5, an outer fiber winding layer 6 and an outer protective layer 7 stacked in sequence;
[0006] The inner surface layer 1 is made of epoxy resin;
[0007] The fibers in the inner fiber cloth reinforcement layer 2, the inner fiber winding layer 3, the fiber reinforced structure layer 4, the outer fiber cloth reinforcement layer 5 and the outer fiber winding layer 6 are basalt fibers respectively;
[0008] The outer protective layer 7 is made of epoxy resin.
[0009] Preferably, the thickness of the inner surface layer 1 is 1 to 2 mm;
[0010] The thickness of the inner fiber cloth reinforcement layer 2 is 0.08-0.12 mm;
[0011] The thickness of the inner fiber winding layer 3 is 0.1 to 1 mm;
[0012] The thickness of the fiber-reinforced structural layer 4 is 1.6 to 45.6 mm;
[0013] The thickness of the outer fiber cloth reinforcement layer 5 is 0.08-0.12 mm;
[0014] The thickness of the outer fiber winding layer 6 is 0.1 to 1 mm;
[0015] The thickness of the outer protective layer 7 is 1-2 mm.
[0016] Preferably, the inner fiber winding layer 3 and the outer fiber winding layer 6 are respectively made of basalt fibers pre-impregnated with epoxy resin.
[0017] Preferably, the mass ratio of epoxy resin to basalt fiber in the basalt fiber pre-impregnated with epoxy resin is 20-40:60-80.
[0018] Preferably, the fiber-reinforced structural layer 4 is composed of basalt fiber chopped yarns, inorganic fillers and resin.
[0019] Preferably, the inorganic filler includes non-metallic minerals with a compressive strength greater than or equal to 40 MPa; the resin includes phenolic resin, vinyl resin, epoxy resin and unsaturated or polyester resin;
[0020] The mass ratio of the basalt fiber chopped yarn, the inorganic filler and the resin is 3-5:60-67:30-35.
[0021] Preferably, the diameter of the composite pipe material is 20 to 10000 mm.
[0022] The present invention also provides a method for preparing the composite pipe material described in the above technical solution, comprising the following steps:
[0023] The raw materials of each layer are used to form a composite tube blank;
[0024] The composite pipe blank is solidified to obtain the composite pipe material.
[0025] Preferably, the molding method includes winding molding;
[0026] The curing temperature is 80-100°C.
[0027] The present invention also provides the use of the composite pipeline material described in the above technical solution or the composite pipeline material prepared by the preparation method described in the above technical solution as a buried pipeline.
[0028] The present invention provides a composite pipe material, which includes an inner surface layer, an inner fiber cloth reinforcement layer, an inner fiber winding layer, a fiber reinforcement structure layer, an outer fiber cloth reinforcement layer, an outer fiber winding layer and an outer protective layer stacked in sequence from the inside to the outside; the inner surface layer is composed of epoxy resin; the fibers in the inner fiber cloth reinforcement layer, the inner fiber winding layer, the fiber reinforcement structure layer, the outer fiber cloth reinforcement layer and the outer fiber winding layer are basalt fibers respectively; the outer protective layer is composed of epoxy resin. In the present invention, epoxy resin and basalt fiber have good electrical insulation and shielding properties, so that the pipeline material has a good anti-stray current effect; the inner surface layer ensures the smoothness, sealing and medium resistance of the pipeline, and prevents medium leakage or eddy current; the inner and outer fiber cloth reinforcement layer structures play a role in enhancing the structural stability, and also play a role in improving the bearing capacity and deformation resistance of the pipe body; the fiber reinforcement structure layer mainly plays a role in improving the rigidity and pressure bearing performance of the pipe body; the outer protective layer mainly plays a role in improving the resistance of the pipe body to stray current and wear resistance. The layers of the entire pipe body structure are tightly bonded to each other, and have both good mechanical properties and anti-stray current capabilities. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the cross-sectional structure of the composite pipe material;
[0030] Figure 2 It is a schematic diagram of the longitudinal section structure of the composite pipe material;
[0031] Among them, 1 is the inner surface layer, 2 is the inner fiber cloth reinforcement layer, 3 is the inner fiber winding layer, 4 is the fiber reinforced structural layer, 5 is the outer fiber cloth reinforcement layer, 6 is the outer fiber winding layer, and 7 is the outer protective layer. DETAILED DESCRIPTION
[0032] The present invention provides a composite pipe material, which comprises, from inside to outside, an inner surface layer 1, an inner fiber cloth reinforcement layer 2, an inner fiber winding layer 3, a fiber reinforced structure layer 4, an outer fiber cloth reinforcement layer 5, an outer fiber winding layer 6 and an outer protective layer 7 which are stacked in sequence.
[0033] As a specific implementation of the present invention, the inner surface layer 1 is made of epoxy resin; the thickness of the inner surface layer 1 can be 1 to 2 mm, specifically 1 mm, 1.5 mm or 2 mm.
[0034] As a specific implementation of the present invention, the thickness of the inner fiber cloth reinforcement layer 2 may be 0.08-0.12 mm, and may be specifically 0.1 mm; the inner fiber cloth reinforcement layer 2 is composed of basalt fiber cloth woven from basalt fiber yarns.
[0035] As a specific embodiment of the present invention, the thickness of the inner fiber winding layer 3 can be 0.1-1 mm, specifically 0.2 mm, 0.3 mm, 0.5 mm, 0.8 mm or 1 mm; the inner fiber winding layer 3 can be composed of basalt fiber pre-impregnated with epoxy resin, and the basalt fiber can be specifically basalt continuous fiber. As a specific embodiment of the present invention, the mass ratio of epoxy resin to basalt fiber in the basalt fiber pre-impregnated with epoxy resin can be 20-40:60-80, or 30-35:70-75, specifically 30:70, 25:75, 20:80.
[0036] As a specific embodiment of the present invention, the thickness of the fiber reinforced structural layer 4 can be 1.6 to 45.6 mm, or 2 to 40 mm, or further 5 to 30 mm; the fiber reinforced structural layer 4 can be composed of basalt fiber chopped yarn, inorganic filler and resin; the inorganic filler can be a non-metallic mineral with a compressive strength greater than or equal to 40 MPa, and can be specifically quartz sand or calcium carbonate, and the maximum particle size of the inorganic filler is less than or equal to one third of the thickness of the fiber reinforced structural layer 4; the resin can include phenolic resin, vinyl resin, epoxy resin or unsaturated polyester resin; the mass ratio of the basalt fiber chopped yarn, inorganic filler and resin can be 3 to 5:60 to 67:30 to 35, or 4:62 to 65:32 to 33, and can be specifically 4:63:33, 4:64:32 or 3:65:33.
[0037] As a specific embodiment of the present invention, the thickness of the outer fiber cloth reinforcement layer 5 can be 0.08-0.12 mm, specifically 0.08 mm, 0.1 mm or 0.12 mm; the outer fiber cloth reinforcement layer 5 can be composed of basalt fiber cloth formed by weaving, coating and fixing basalt fiber yarn. The present invention has no special requirements for the weaving, coating and fixing, and the conventional methods in the art can be used. As a specific embodiment of the present invention, the thickness and composition of the outer fiber cloth reinforcement layer 5 can be consistent with those of the inner fiber cloth reinforcement layer 2.
[0038] As a specific embodiment of the present invention, the thickness of the outer fiber winding layer 6 can be 0.1-1 mm, specifically 0.1 mm, 0.2 mm, 0.3 mm or 0.5 mm; the outer fiber winding layer 6 can be composed of basalt fiber pre-impregnated with epoxy resin; the basalt fiber can be basalt continuous fiber; the mass ratio of epoxy resin to basalt fiber in the basalt fiber pre-impregnated with epoxy resin can be 20-40:60-80, or 30-35:70-75, specifically 30:70, 25:75, 20:80. As a specific embodiment of the present invention, the thickness and composition of the outer fiber winding layer 6 can be consistent with those of the inner fiber winding layer 3.
[0039] As a specific implementation of the present invention, the outer protective layer 7 is made of epoxy resin; the thickness of the outer protective layer 7 can be 1 to 2 mm, specifically 1 mm, 1.5 mm or 2 mm.
[0040] As a specific implementation of the present invention, the diameter of the composite pipe material may be 20 to 10000 mm, or 50 to 800 mm, and may specifically be 22.6 mm, 27.66 mm, or 35.16 mm.
[0041] Figure 1 It is a schematic diagram of the cross-sectional structure of the composite pipe material. Figure 2 It is a schematic diagram of the longitudinal cross-section structure of the composite pipe material, wherein 1 is the inner surface layer, 2 is the inner fiber cloth reinforcement layer, 3 is the inner fiber winding layer, 4 is the fiber reinforced structural layer, 5 is the outer fiber cloth reinforcement layer, 6 is the outer fiber winding layer, and 7 is the outer protective layer.
[0042] The present invention also provides a method for preparing the composite pipe material described in the above technical solution, comprising the following steps:
[0043] The raw materials of each layer are used to form a composite tube blank;
[0044] The composite pipe blank is solidified to obtain the composite pipe material.
[0045] The present invention utilizes each layer of raw materials to form a composite pipe blank. As a specific embodiment of the present invention, the forming method may include winding forming. In the present invention, the composite pipe prepared by the winding forming process has an inner diameter of ≥1m and a large ring stiffness (≥7000N / m 2 ), hoop tensile strength ≥ 250MPa and Barcol hardness ≥ 35.
[0046] As a specific embodiment of the present invention, the winding molding may include the following steps:
[0047] Coating epoxy resin on the surface of the rotatable inner core mold to form an inner surface layer 1;
[0048] Wrapping basalt fiber cloth on the surface of the inner surface layer 1 to form an inner fiber cloth reinforcement layer 2;
[0049] Winding basalt fibers pre-impregnated with epoxy resin on the surface of the inner fiber cloth reinforcement layer 2 to form an inner fiber winding layer 3;
[0050] Spreading a premix of basalt fiber chopped yarn, inorganic filler and resin on the surface of the inner fiber winding layer 3 to form a fiber reinforced structure layer 4;
[0051] Wrap basalt fiber cloth on the surface of the fiber reinforced structural layer 4 to form an outer fiber cloth reinforcement layer 5;
[0052] Basalt fibers pre-impregnated with epoxy resin are wound on the surface of the outer fiber cloth reinforcement layer 5 to form an outer fiber winding layer 6;
[0053] Epoxy resin is coated on the surface of the outer fiber winding layer 6 to form an outer protective layer 7 to obtain a composite tube blank.
[0054] As a specific embodiment of the present invention, the winding method of the basalt fiber wrapped with pre-impregnated epoxy resin during the winding process can be cross-reciprocating winding, which can maximize the mechanical strength (circumferential and axial) of the pipeline, and the three-dimensionally enhanced pipe wall structure improves the rigidity and bending resistance of the pipeline, resists soil friction, and is not easy to de-wire. The present invention has no special restrictions on other process conditions in the winding process, and conventional methods in the field can be used.
[0055] After the composite pipe blank obtained by winding is solidified, the method may further include: demoulding the solidified product (removing the inner core mold) to obtain a composite pipe material.
[0056] After obtaining the composite tube blank, the present invention solidifies the composite tube blank to obtain the composite pipe material. As a specific embodiment of the present invention, the solidification temperature can be 80-100°C, or 85-95°C, and can be specifically 80°C, 85°C, 90°C, 95°C or 100°C; the solidification time can be 20-30h, and can be specifically 20h, 22h, 24h, 26h, 28h or 30h.
[0057] The present invention also provides the use of the composite pipeline material described in the above technical solution or the composite pipeline material prepared by the preparation method described in the above technical solution as a buried pipeline.
[0058] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0059] Example 1
[0060] Preparation of 22.6mm thick composite pipe material by winding molding process:
[0061] Coating epoxy resin on the surface of the rotatable inner core mold to form an inner surface layer 1 with a thickness of 1 mm;
[0062] The inner surface layer 1 is wrapped with basalt fiber cloth to form an inner fiber cloth reinforcement layer 2 with a thickness of 0.1 mm;
[0063] Basalt continuous fibers pre-impregnated with epoxy resin (the mass ratio of epoxy resin to basalt continuous fibers is 30:70) are wound crosswise and reciprocatingly on the surface of the inner fiber cloth reinforcement layer 2 to form an inner fiber winding layer 3 with a thickness of 0.2 mm;
[0064] A premix of basalt fiber chopped yarn, quartz sand with a maximum particle size of 5 mm and epoxy resin (basalt fiber chopped yarn, inorganic filler and epoxy resin are mixed in a mass ratio of 4:63:33) is spread on the surface of the inner fiber winding layer 3 to form a fiber reinforced structure layer 4 with a thickness of 20 mm;
[0065] Basalt fiber cloth (basalt fiber cloth formed by weaving, coating and fixing basalt fiber yarn) is wrapped on the surface of the fiber reinforced structural layer 4 to form an outer fiber cloth reinforcement layer 5 with a thickness of 0.1 mm;
[0066] Basalt fibers pre-impregnated with epoxy resin (the mass ratio of epoxy resin to basalt continuous fibers is 30:70) are wound crosswise and reciprocatingly on the surface of the outer fiber cloth reinforcement layer 5 to form an outer fiber winding layer 6 with a thickness of 0.2 mm;
[0067] Epoxy resin is coated on the surface of the outer fiber winding layer 6 to form an outer protective layer 7 with a thickness of 1 mm, thereby obtaining a composite tube blank;
[0068] The composite pipe blank was cured at 100° C. for 24 hours, and then the inner core mold was removed to obtain a composite pipe material with a thickness of 22.6 mm.
[0069] Example 2
[0070] Composite pipe material with a thickness of 27.66 mm was prepared by winding molding process:
[0071] Coating epoxy resin on the surface of the rotatable inner core mold to form an inner surface layer 1 with a thickness of 1.5 mm;
[0072] The inner surface layer 1 is wrapped with basalt fiber cloth to form an inner fiber cloth reinforcement layer 2 with a thickness of 0.12 mm;
[0073] Basalt continuous fibers pre-impregnated with epoxy resin (the mass ratio of epoxy resin to basalt continuous fibers is 25:75) are wound crosswise and reciprocatingly on the surface of the inner fiber cloth reinforcement layer 2 to form an inner fiber winding layer 3 with a thickness of 0.3 mm;
[0074] A premix of basalt fiber chopped yarn, quartz sand with a maximum particle size of 6 mm and epoxy resin (basalt fiber chopped yarn, inorganic filler and epoxy resin are mixed in a mass ratio of 3:65:33) is spread on the surface of the inner fiber winding layer 3 to form a fiber reinforced structure layer 4 with a thickness of 24 mm;
[0075] Basalt fiber cloth (basalt fiber cloth formed by weaving, coating and fixing basalt fiber yarn) is wrapped on the surface of the fiber reinforced structural layer 4 to form an outer fiber cloth reinforcement layer 5 with a thickness of 0.12 mm;
[0076] Basalt fibers pre-impregnated with epoxy resin are wound in a cross-reciprocating manner on the surface of the outer fiber cloth reinforcement layer 5 (the mass ratio of epoxy resin to basalt continuous fibers is 25:75, forming an outer fiber winding layer 6 with a thickness of 0.12 mm;
[0077] Epoxy resin is coated on the surface of the outer fiber winding layer 6 to form an outer protective layer 7 with a thickness of 1.5 mm, thereby obtaining a composite tube blank;
[0078] After the composite pipe blank was cured at 100° C. for 24 hours, the inner core mold was removed to obtain a composite pipe material with a thickness of 27.66 mm.
[0079] Example 3
[0080] Composite pipe material with a thickness of 35.16 mm was prepared by winding process:
[0081] Coating epoxy resin on the surface of the rotatable inner core mold to form an inner surface layer 1 with a thickness of 2.0 mm;
[0082] Basalt fiber cloth is wrapped on the surface of the inner surface layer 1 to form an inner fiber cloth reinforcement layer 2 with a thickness of 0.08 mm;
[0083] Basalt continuous fibers pre-impregnated with epoxy resin (the mass ratio of epoxy resin to basalt continuous fibers is 20:80) are wound crosswise and reciprocatingly on the surface of the inner fiber cloth reinforcement layer 2 to form an inner fiber winding layer 3 with a thickness of 0.5 mm;
[0084] A premix of basalt fiber chopped yarn, quartz sand with a maximum particle size of 7 mm and epoxy resin (basalt fiber chopped yarn, inorganic filler and epoxy resin are mixed in a mass ratio of 4:64:32) is spread on the surface of the inner fiber winding layer 3 to form a fiber reinforced structure layer 4 with a thickness of 30 mm;
[0085] Basalt fiber cloth (basalt fiber cloth formed by weaving, coating and fixing basalt fiber yarn) is wrapped on the surface of the fiber reinforced structural layer 4 to form an outer fiber cloth reinforcement layer 5 with a thickness of 0.08 mm;
[0086] Basalt fibers pre-impregnated with epoxy resin (the mass ratio of epoxy resin to basalt continuous fibers is 20:80) are wound crosswise and reciprocatingly on the surface of the outer fiber cloth reinforcement layer 5 to form an outer fiber winding layer 6 with a thickness of 0.5 mm;
[0087] Epoxy resin is coated on the surface of the outer fiber winding layer 6 to form an outer protective layer 7 with a thickness of 2.0 mm, thereby obtaining a composite tube blank;
[0088] After the composite pipe blank was cured at 100° C. for 24 hours, the inner core mold was removed to obtain a composite pipe material with a thickness of 35.16 mm.
[0089] Comparative Example 1
[0090] Take carbon steel pipe as a comparison example.
[0091] The pipeline performance of Examples 1 to 2 and Comparative Example 1 was tested according to the following method, and the results are listed in Table 1:
[0092] (1) Buckle hardness
[0093] Refer to "Barcol hardness test method for reinforced plastics" (GB T 3854-2017).
[0094] Sample preparation: Thickness 24mm, length and width should satisfy that the distance between any pressure point and the edge of the sample and between pressure points should not be less than 3mm, ensuring that the surface of the sample is smooth and flat, without defects and mechanical damage.
[0095] Test steps: Place the sample on a hard and stable supporting surface cement platform for testing. The product can be tested directly on the appropriate part of its surface. The curved surface sample should be supported stably. Place the indenter sleeve vertically on the sample surface, and place the support feet on the same surface or other solid materials with the same height, and keep the indenter and the support feet on the same plane. Hold the hardness tester housing with your hand, and quickly and evenly apply pressure downward until the dial reading reaches the maximum value. Record the maximum reading, which is the Barcol hardness value. When the indenter contacts the surface to be tested, avoid sliding and scratching, and test the hardness at least in 10 different positions of the sample.
[0096] (2) Initial ring stiffness
[0097] Refer to "Test method for parallel plate external load performance of fiber reinforced thermosetting plastic pipes" (GBT5352-2005).
[0098] Sample preparation: The length of the sample prepared by vertically cutting the end of the sample should be 300mm to ensure smooth cutting. Each group of samples consists of 3 pieces.
[0099] Test steps: Place in an environment with a temperature of (23 ± 2) ℃ for 4 hours, and conduct the test in the same environment. The surface of the loading plate should be flat and smooth. The thickness of the plate should not be less than 6mm to ensure sufficient rigidity. The length of the plate should not be less than the length of the specimen, and the width should not be less than the contact width of the specimen with the loading plate when the specimen reaches the maximum radial deformation plus 150mm. Place the specimen at the center of the loading plate. Install the deformation measuring instrument in a suitable position. Apply the initial load to make the upper loading plate contact the specimen. Check and adjust the deformation measurement system to make the entire system in normal working condition, which is used as the starting point for measuring deformation. Load the specimen at the loading speed specified in 5.5. Continuous or interval measurement can be adopted when measuring the load-deformation curve. The deformation increment of the interval measurement should not be greater than 5% of the average inner diameter of the specimen. Pay attention to the first significant event that occurs, and record the type, location and corresponding load and deformation of the event in time.
[0100] (3) Hoop tensile strength
[0101] Refer to "Test method for mechanical properties of fiber-wound reinforced plastic ring specimens" (GB / T1458-2023).
[0102] Sample preparation: The fiber-wound reinforced composite pipe sample is a ring sample cut directly from the fiber-wound reinforced composite pipe, and then machined to ensure that the radius of the reduction surface r is not less than 9mm, the minimum width of the reduction surface is not less than 14mm, and the sample width L is not less than 23mm. The two reduction surfaces are at a distance of 180°, and the cross section is at the center relative to the sample width. Each group of samples has 5.
[0103] Test steps: The fiber-wound reinforced composite pipe sample uses a type II fixture. The width of the tension disk should be greater than the width of the sample, and the diameter is close to the inner diameter of the sample. The loading speed of the fiber-wound reinforced composite pipe sample is 2.5mm / min~12.5mm / min. The reduced surface of the fiber-wound reinforced composite pipe sample is aligned with the gap of the tension disk, and the contact surface between the sample and the fixture should be lubricated. Apply load to the sample evenly and continuously until it is destroyed, and record the failure load.
[0104] (4) Corrosion rate
[0105] Refer to "Method for Evaluation of Residual Strength of Defective Oil and Gas Pipelines" (Y / T 6477-2017).
[0106] A group of composite pipelines and a group of petroleum carbon steel pipelines were buried in the test section, and the point thickness measurement method (PTR) was used. The observation period was 3 years.
[0107] Test steps: Use a wall thickness gauge to measure the wall thickness of the test area to determine the minimum measured wall thickness and average wall thickness. Perform the test every six months for three consecutive years and calculate the corrosion rate.
[0108] Table 1 Properties of composite pipes
[0109]
[0110] The corrosion rate refers to the speed at which a material corrodes in a corrosive medium, which can indirectly prove the material's ability to resist stray current. The corrosion rate is an indicator of how fast a material corrodes under specific environmental conditions. In a stray current environment, the corrosion rate can reflect the degree to which the material is affected by the stray current; the smaller the corrosion rate, the smaller the degree of influence of the stray current.
[0111] It can be seen from Table 1 that the composite pipeline material provided by the present invention has the characteristics of light weight and high strength, and can well reduce corrosion caused by stray current.
[0112] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A composite pipe material, characterized in that: The invention comprises, from the inside to the outside, an inner surface layer (1), an inner fiber cloth reinforcement layer (2), an inner fiber winding layer (3), a fiber reinforcement structure layer (4), an outer fiber cloth reinforcement layer (5), an outer fiber winding layer (6) and an outer protective layer (7) which are stacked in sequence; The inner surface layer (1) is composed of epoxy resin; The fibers in the inner fiber cloth reinforcement layer (2), the inner fiber winding layer (3), the fiber reinforced structure layer (4), the outer fiber cloth reinforcement layer (5) and the outer fiber winding layer (6) are basalt fibers respectively; The outer protective layer (7) is made of epoxy resin.
2. The composite pipe material according to claim 1, characterized in that: The thickness of the inner surface layer (1) is 1 to 2 mm; The thickness of the inner fiber cloth reinforcement layer (2) is 0.08-0.12 mm; The thickness of the inner fiber winding layer (3) is 0.1 to 1 mm; The thickness of the fiber-reinforced structural layer (4) is 1.6 to 45.6 mm; The thickness of the outer fiber cloth reinforcement layer (5) is 0.08-0.12 mm; The thickness of the outer fiber winding layer (6) is 0.1 to 1 mm; The thickness of the outer protective layer (7) is 1 to 2 mm.
3. The composite pipe material according to claim 1 or 2, characterized in that: The inner fiber winding layer (3) and the outer fiber winding layer (6) are respectively composed of basalt fibers pre-impregnated with epoxy resin.
4. The composite pipe material according to claim 3, characterized in that: The mass ratio of epoxy resin to basalt fiber in the basalt fiber pre-impregnated with epoxy resin is 20-40:60-80.
5. The composite pipe material according to claim 1 or 2, characterized in that: The fiber-reinforced structural layer (4) is composed of basalt fiber chopped yarns, inorganic fillers and resin.
6. The composite pipe material according to claim 5, characterized in that: The inorganic filler includes non-metallic minerals with a compressive strength greater than or equal to 40 MPa; the resin includes phenolic resin, vinyl resin, epoxy resin and unsaturated or polyester resin; The mass ratio of the basalt fiber chopped yarn, the inorganic filler and the resin is 3-5:60-67:30-35.
7. The composite pipe material according to claim 1, characterized in that: The diameter of the composite pipe material is 20 to 10000 mm.
8. The method for preparing the composite pipe material according to any one of claims 1 to 7, comprising the following steps: The raw materials of each layer are used to form a composite tube blank; The composite pipe blank is solidified to obtain the composite pipe material.
9. The preparation method according to claim 8, characterized in that: The molding method includes winding molding; The curing temperature is 80-100°C.
10. Use of the composite pipe material according to any one of claims 1 to 7 or the composite pipe material prepared by the preparation method according to claim 8 or 9 as a buried pipe.
Citation Information
Patent Citations
Exhaust pipeline prepared from basalt fibers and manufacturing method of exhaust pipeline
CN118997903A
Method of making pipe using basalt fiber as reinforcing material
CN1426888A
Basalt fiber pipe body
CN213809266U
Basalt fiber double-reinforced polyethylene pipeline
CN219994628U
Composite pipeline material
CN223605225U